Descarte de embalagens secundarias pelos supermercados: estudo de multiplos casos na cidade de São Paulo - Silva, Leticia Lima Salazar e (2018)
Secondary packaging is one of the materials most found in urban waste, because it is essential in modern consumer society. It groups several primary packaging (final packaging to the customer) and serves to protect the products, to facilitate the transportation and storage in the route between the manufacturer and the point of sale, in the case of this work, the supermarket. After receiving the products at the store, this kind of packaging is disposed. Therefore there is a large volume of this type of packaging that makes up the so-called solid waste that can be recycled. By means a multiple case study, the objective of this work is to verify if the Brazilian supermarkets dispose the packaging of secondary level in an environmentally adequate way, besides evaluating if the practices of disposal of those packages present common or diverse characteristics depending on the structure and income of the supermarket considered. For this purpose, it was made a bibliographic research to identify the best practices that indicates the correct destination of the secondary packaging. After storage and transportation, the secondary packaging loses its function and becomes solid waste, but this does not mean that is an useless material. On the contrary, this type of garbage can generate income for the supermarket or for cooperatives of people in a position of social vulnerability. As conclusion of this work, it can be verified that the researched supermarkets are following practices already adopted in first-world supermarkets, in alignment with European models according to the literature review. However, it is found that this behavior is mainly verified in multinational companies, where the head office adopts a sustainability program. Brazilian capital supermarkets also recycle the packages as multinational ones do but the breadth of their programs are not as comprehensive in terms of sustainability and are limited to the recycling of secondary packaging.